2019
DOI: 10.1108/nfs-07-2018-0193
|View full text |Cite
|
Sign up to set email alerts
|

Students’ knowledge and attitudes towards GMOs and nanotechnology

Abstract: Purpose The purpose of this paper is to investigate knowledge and attitudes toward genetically modified organisms (GMOs) and nanotechnology among the Canadian youth demographic. The primary objective of this pilot study was to investigate the knowledge and attitudes toward GMOs and nanotechnology among first year university students. The secondary objective was to compare knowledge and attitudes toward GMOs and nanotechnology among students studying nutrition as to students who do not study nutrition. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Because consideration, awareness and knowledge of dental erosion provided as part of the education of these two disciplines might be beneficial to developing strategies for improved collaboration, this study was planned and conducted. The questionnaire developed by the researchers was used in conducting this study, similar to the various studies evaluating students' attitudes and behaviors on different subjects (Soni et al , 2018; Hamilton and Hekmat, 2018; Hekmat and Dawson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Because consideration, awareness and knowledge of dental erosion provided as part of the education of these two disciplines might be beneficial to developing strategies for improved collaboration, this study was planned and conducted. The questionnaire developed by the researchers was used in conducting this study, similar to the various studies evaluating students' attitudes and behaviors on different subjects (Soni et al , 2018; Hamilton and Hekmat, 2018; Hekmat and Dawson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, educational background has been shown to influence GM food attitudes: e.g. life scientists were more favourable towards GMOs (Scott et al , 2018), while those with a nutrition background were more aware of, though not necessarily more positive about GM food (Hekmat and Dowson, 2018). The importance of educational background was further emphasized in consumer research with youth (Florek-Łuszczki et al , 2016), with studies demonstrating a positive influence of biology-related education (Maes et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The questions regarding attitudes toward GMOs showed that overall both populations either felt unsure or held negative attitudes about GMOs. However, theme analysis of open-ended responses showed that the students studying nutrition were less apprehensive of GMOs in general (Hekmat and Dawson, 2019). Therefore, educational background in terms of college majors and classes taken can lead to differing perceptions related to biotechnology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following methods of similar university-based studies, we attempt to understand perceptions of novel phenomena in the food system and suggest that future research expand upon our research by way of a larger sample size with wider demographics. While past research has studied labeling, value-based attributes of food and preferences among university students (Silva et al ., 2019; Hillmire and Schnitker, 2020), including specifically GMO and GMO-free labels (Oselinsky et al ., 2021), and others have assessed students' knowledge and attitudes of GMOs (Hekmat and Dawson, 2019), our research will look at perceptions and consumer preferences related to the new bioengineered label and associated terminology.…”
Section: Introductionmentioning
confidence: 99%